The effect of ESG performance on stock price volatility: A study of emerging markets in Asia - Kurniawan, Marlina; Husodo, (BISMA (Bisnis dan Manajemen), 2023)
This study aims to investigate the influence of Environmental, Social, and Governance (ESG) on the volatility of stock prices for public firms in emerging Asia. This study uses the selection of ESG score data and employs multiple regression, dummy variables, and Difference-in-Differences (DID) models using Coronavirus Disease 2019 (COVID-19), an exogenous event. This study uses two periods to compare the volatility of stock prices before and after COVID-19, which are 2020 and 2021. Meanwhile, this study examines the volatility of a firm based on its ESG performance over one year. Therefore, this study uses the ESG score in 2019 and 2020. There are three findings from this study. First, this study indicates that firms with higher ESG performance have less volatility than firms with lower ESG performance. Second, the findings indicate that higher ESG performance, as opposed to lower ESG performance, mitigates the increase in stock price volatility caused by the COVID-19 shock. Third, ESG performance helps to stabilise stock prices. The analysis of the effect of ESG performance on the volatility of stock prices in this article is supported by new empirical data, which also includes suggestions for businesses and investors. This research has several implications. First, the study implies that firms can enhance profitability by actively improving their ESG performance through initiatives like renewable energy adoption, equitable wages, and strong governance practices. Second, investors are also encouraged to prioritise firms with robust ESG performance.